A web based smart city tour application for tourists around the globe - Obonyo, John Oduor (Strathmore University, 2021)
The number of people on tours has been increasing around the world, continuing to strengthen and develop the tourism industry. With many cities and attraction sites around the globe, tourists might only have quality information about a few. This creates a challenge of the quality of information, in terms of time and accuracy, that tourists get when they visit new places. The current systems that are used do not facilitate provision of timely and accurate information, for some, to the tourists when on the move. The proposed system plans to solve this challenge by creating a smart application that will be used by tourists around the globe. The application will allow users to fill in their interests while on tours anywhere around the world, then it analyses those interests and create a travelling schedule for the users of the place they are visiting based on what they like. The proposed system will be a web-based application that uses HTML, PHP, CSS, and JavaScript programming technique. Data and information will be stored in a database connected to the system. The MySQL database management system will be used to create, manage, and maintain the database. Google Maps and PHP Mailer APIs will be used to fetch the users’ location and send some reminder emails to the user. The system will be developed using the Prototyping System Development method. This method will allow for continuous revision of the system as progress is made in development. This will enable achieving a quality system that meets the user’s requirements.
An Information System Project Proposal submitted to the Faculty of Information Technology in partial fulfilment of the requirements for the award of a Degree in Business Information Technology